2002
DOI: 10.1104/pp.002717
|View full text |Cite
|
Sign up to set email alerts
|

Differential Accumulation of Dimethylallyl Diphosphate in Leaves and Needles of Isoprene- and Methylbutenol-Emitting and Nonemitting Species

Abstract: The biosynthesis and emission of volatile plant terpenoids, such as isoprene and methylbutenol (MBO), depend on the chloroplastic production of dimethylallyl diphosphate (DMAPP). To date, it has been difficult to study the relationship of cellular DMAPP levels to emission of these volatiles because of the lack of a sensitive assay for DMAPP in plant tissues. Using a recent DMAPP assay developed in our laboratories, we report that species with the highest potential for isoprene and MBO production also exhibit e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 59 publications
1
59
3
Order By: Relevance
“…Correspondingly the k cat , being a direct measure of the catalytic efficiency, was found to be relatively low for isoprene synthase, similar to those of other allylic diphosphate-utilizing enzymes (Table 2). In mature oak leaves (Quercus robur) the calculated chloroplastidic DMAPP concentrations were found to be close to the apparent K m value of oak isoprene synthase (Lehning et al 1999;Rosenstiel et al 2002), supporting the hypothesis that the availability of DMAPP can be one of the major driving forces of isoprene synthase activity in mature leaves. The production of the intermediates is light-induced and a positive correlation between leaf DMAPP levels (as substrate for isoprene synthase) and photosynthate flux led to the hypothesis that the lightdependence of isoprene emission is in part due to controls over DMAPP production and content (Brüggemann & Schnitzler 2002a, b;Rosenstiel et al 2002).…”
Section: Link Between Isoprene Emission Capacity and Gross Photosynthmentioning
confidence: 53%
See 3 more Smart Citations
“…Correspondingly the k cat , being a direct measure of the catalytic efficiency, was found to be relatively low for isoprene synthase, similar to those of other allylic diphosphate-utilizing enzymes (Table 2). In mature oak leaves (Quercus robur) the calculated chloroplastidic DMAPP concentrations were found to be close to the apparent K m value of oak isoprene synthase (Lehning et al 1999;Rosenstiel et al 2002), supporting the hypothesis that the availability of DMAPP can be one of the major driving forces of isoprene synthase activity in mature leaves. The production of the intermediates is light-induced and a positive correlation between leaf DMAPP levels (as substrate for isoprene synthase) and photosynthate flux led to the hypothesis that the lightdependence of isoprene emission is in part due to controls over DMAPP production and content (Brüggemann & Schnitzler 2002a, b;Rosenstiel et al 2002).…”
Section: Link Between Isoprene Emission Capacity and Gross Photosynthmentioning
confidence: 53%
“…On the other hand the demand for DMAPP is very high during leaf expansion by simultaneous investment in growth and greening, as DMAPP is one of the essential precursors of all plant terpenoids (about 30 000 have been identified in leaves), among them those needed for the assembly of the photosynthetic apparatus. Indeed Rosenstiel et al (2002) found that young leaves of cotton wood contained significantly lower levels of DMAPP than mature leaves. Due to the high K m value of isoprene synthase, poor substrate availability due to partitioning to competing pathways may prevent isoprene synthase to be active.…”
Section: Link Between Isoprene Emission Capacity and Gross Photosynthmentioning
confidence: 99%
See 2 more Smart Citations
“…In Populus sp. a link between low NO 3 − and isoprene has been established (7) and other work indicates that DMAPP levels may govern the rate of emission (31,32).…”
Section: Raɵo M/z 640/( 577+640)mentioning
confidence: 99%